The Violation of Fundamental Human Rights by Limiting Legal Capacity of an Adult (Law and world, 2020)
Within this article we’ve considered the disposition of the Article 16 of the Civil Code of Georgia, it’s aim and connection with human rights protected under the Constitution. After analyzing case law and scientific literature, it seems that it is possible to limit the legal capacity of a person at the age of majority, if the adult abuses alcohol or narcotic substances and by doing so, puts his/her family in material hardship, however, it’s unclear why it is necessary to limit legal capacity for only alcohol and drug users. Meanwhile, Georgian legislation, with other means of law obliges person to care for his/her family’s material condition. If a person avoids to undertake the obligation to pay maintenance, it is possible to force him/her to pay it according to the decision of a court. (Court can demand a person to fulfill the obligation to pay maintenance for his/her family members in order to prevent material hardship). The purposes of provisions which are limiting legal capacity are vague (GCC Article 16, Chapter of Special Proceeding of Civil Procedure Code of Georgia), it’s possible to protect family’s material condition without im- posing these measures while not limiting person’s constitutional rights. In the article, we’ve also discussed the premises of limiting legal capacity and consequences, when there is a possibility of violation of human rights protected by the constitution such as: human dignity, right to free personal development, right to equality and right to property. It is possible that family members may be engaged in material hardship not only by the person who has an addiction to alcohol and drugs, but also by a person with no such characteristics. Accordingly, it is wrong and unequal to limit legal capacity only for persons, which have an addiction to illegal substances and alcohol. Besides, the achievement of the legitimate aim, under the GCC Article 16, is possible by the less intrusive measures.